Effects of a lumbar exoskeleton that provides two traction forces on spinal loading and muscles - Qi, Kaicheng; Yin, Zhiyang; Li, Chao; Zhang, Jianjun; Song, Jingke (Frontiers in Bioengineering and Biotechnology, 2025)
In workplaces with prolonged or repetitive stooping, disc herniation due to excessive pressure at the lumbar L5/S1 joints has been a difficult condition to prevent and treat in the field of lower back pain. Previous research on lumbar exoskeletons mainly focused on the impact of assistive torque on muscle activation, overlooking the fact that providing assistive torque is not the optimal approach when bending over with a low load. Instead, using traction force to reduce disc pressure is a more adaptable method to mitigate the risk of intervertebral disc herniation. In this paper, a novel lumbar exoskeleton mechanism is proposed. The exoskeleton principle is similar to a lever arranged on the torso, which provides two types of traction forces using a single compression spring with a lower support moment and higher traction performance. Subsequently, a kinetic simulation model covering passive physiologic tissues and spring stiffness was developed to determine the optimal range of traction forces for a given load, to predict the disc pressure and muscle activation at optimal traction forces. Eight subjects were invited to wear the exoskeleton for stooping and lifting tests under extreme loads, using myoelectric sensors to measure muscle activation. The results confirm that optimal traction force effectively reduces L5/S1 disc pressure without additionally increasing muscle activation. The exoskeleton in this study provides an alternative idea for the design of lumbar exoskeletons adapted to light load stooping.